2004
DOI: 10.1185/030079903125002595
|View full text |Cite
|
Sign up to set email alerts
|

Waist-hip ratio and low HDL predict the risk of coronary artery disease in Pakistanis

Abstract: The cardiovascular risk profile in this population is consistent with metabolic syndrome where low HDL and WHR can be used to predict the risk of CAD. Results suggest the need to redefine the currently practised approach to CAD management in this population to fit local needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 37 publications
5
43
1
Order By: Relevance
“…A large body of evidence has established total and LDL cholesterol as important cardiovascular risk factors, in particular among patients with diabetes (2,6,34). However, in parallel to the results of our prospective study, no significant associations between high total or LDL cholesterol and the presence of CAD have been found in cross-sectional angiographic investigations (27,28,35). Among our coronary patients, 31.3% were on statins.…”
Section: Lipid Risk Factors In Diabetes and Ifgsupporting
confidence: 61%
“…A large body of evidence has established total and LDL cholesterol as important cardiovascular risk factors, in particular among patients with diabetes (2,6,34). However, in parallel to the results of our prospective study, no significant associations between high total or LDL cholesterol and the presence of CAD have been found in cross-sectional angiographic investigations (27,28,35). Among our coronary patients, 31.3% were on statins.…”
Section: Lipid Risk Factors In Diabetes and Ifgsupporting
confidence: 61%
“…First, the study is estimating the impact of various modifiable risk factors for MI that should be of considerable relevance to the prevention and control of cardiovascular disease in Pakistan, including, as noted above, tobacco consumption, dietary intake, and physical activity [5,6,22,23]. The second focus of PROMIS is to contribute to scientific (particularly genetic) discovery in an ethnicspecific context.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic disease correlates with low HDL, waist-hip ratio, markers of inflammation and insulin resistance [15] and reduced glomerular filtration rate [16] in this Pakistani cohort of Indian Asians. A previous work in the field of M-IRS has suggested that the previous World Health Organisation definition (Table 1) [17] was a better predictor of risk of diabetes and cardiovascular disease compared to NCEP in Caucasians and also that the IDF definition predicted cardiovascular risk better in Caucasian women [18].…”
Section: Discussionmentioning
confidence: 98%
“…The study cohort consisted of 400 patients recruited with ethical consent who underwent coronary angiography from 1998 to 2001 for presenting symptoms of chest pain [8]. Two groups were selected based on the presence of significant CAD as defined by a 50% stenosis in one or more coronary arteries and an age-and sex-matched control group presenting with similar symptoms but with no angiographic evidence of disease.…”
Section: Methodsmentioning
confidence: 99%